Nominal and real interest rates during an optimal disinflation in New Keynesian models. - Marcus Hagedorn (European Central Bank (ECB), 2008)
Central bankers' conventional wisdom suggests that nominal interest rates should be raised to implement a lower inflation target. In contrast, I show that the standard New Keynesian monetary model predicts that nominal interest rates should be decreased to attain this goal. Real interest rates, however, are virtually unchanged. These results also hold in recent vintages of New Keynesian models with sticky wages, price and wage indexation and habit formation in consumption.
Keywords: E41; E43; E51; E52; 330; Disinflation; nominal and real interest rates; optimal monetary policy; Inflationsbekämpfung; Zins; Lohnrigidität; Preisrigidität; Neoklassische Synthese; Theorie